Selective HDAC6 inhibition decreases early stage of lupus nephritis by down-regulating both innate and adaptive immune responses. (16th October 2017) - Ren, J; Liao, X; Vieson, M D; Chen, M; Scott, R; Kazmierczak, J; Luo, X M; Reilly, C M
Summary: We have demonstrated previously that histone deacetylase (HDAC6) expression is increased in animal models of systemic lupus erythematosus (SLE) and that inhibition of HDAC6 decreased disease. In our current studies, we tested if an orally active selective HDAC6 inhibitor would decrease disease pathogenesis in a lupus mouse model with established early disease. Additionally, we sought to delineate the cellular and molecular mechanism(s) of action of a selective HDAC6 inhibitor in SLE. We treated 20-week-old (early-disease) New Zealand Black (NZB)/White F1 female mice with two different doses of the selective HDAC6 inhibitor (ACY-738) for 5 weeks. As the mice aged, we determined autoantibody production and cytokine levels by enzyme-linked immunosorbent assay (ELISA) and renal function by measuring proteinuria. At the termination of the study, we performed a comprehensive analysis on B cells, T cells and innate immune cells using flow cytometry and examined renal tissue for immune-mediated pathogenesis using immunohistochemistry and immunofluorescence. Our results showed a reduced germinal centre B cell response, decreased T follicular helper cells and diminished interferon (IFN)-γ production from T helper cells in splenic tissue. Additionally, we found the IFN-α-producing ability of plasmacytoid dendritic cells was decreased along with immunoglobulin isotype switching and the generation of pathogenic autoantibodies. Renal tissue showed decreased immunoglobulin deposition and reduced inflammation as judged by glomerular and interstitial inflammation. Taken together, these studies show selective HDAC6 inhibition decreased several parameters of disease pathogenesis in lupus-prone mice. The decrease was due in part to inhibition of B cell development and response. Graphical Abstract: